Effect of Heat Stress on the Behavior of Lactating Cows Housed in Compost Barns: A Systematic Review - Frigeri, Karen Dal’ Magro; Deniz, Matheus [UNESP]; Damasceno, Flávio Alves; Barbari, Matteo; Herbut, Piotr; Vieira, Frederico Márcio Corrêa (MDPI, 2023)
In this study, we performed a systematic review to assess the effect of thermal stress on the behavior of lactating cows housed in compost barns. Peer-reviewed articles written in English that evaluated the effect of heat stress on the behavior of lactating cows raised in compost barns were used in this systematic review. The resulting articles (38) underwent a four-step PRISMA appraisal process and resulted in six articles that fitted our inclusion criteria. Our review highlighted that the temperature and humidity index prevailed among the studies to evaluate thermal comfort. Regarding the behavior, heat stress promoted decreases in feed events and the time that cows spent lying down. In contrast, there was an increase in events of visiting the water trough, the number of steps, agonistic behavior, and dyspnea. In conclusion, heat stress affected the behavior of lactating cows raised in compost barns; however, some care is needed in extrapolating our findings since this is a recent research area and further studies are needed.
Keywords: applied ethology; cattle; confined system; temperature-humidity-index; thermal comfort; zero-grazing system